Recent developments of TiO2 photocatalysis involving advanced oxidation and reduction reactions in water. Issue 6 (December 2018) - Athanasekou, Chrysoula P.; Likodimos, Vlassis; Falaras, Polycarpos
Graphical abstract: Abstract: Advanced nanostructures of titanium dioxide are intensively investigated for environmental protection. The latest developments in the field pay special attention to innovative and highly performing titania materials (anatase/rutile mixed-phase nanocomposites, anion-doped core-shell nanostructures, self-organized nanotubes, photonic crystals and their modifications with graphene oxide and metal nanoparticles) with original functionalities and tailored properties (visible light activated photocatalysts-VLA), the elucidation of the corresponding mechanisms involving interaction of light with matter at the nanoscale and resulting photoinduced electron transfer reactions. These materials are also considered as key components for the design and fabrication of devices (photocatalytic reactors) for efficient degradation and/or transformation of emerging environmental contaminants. The presence of a TiO2 photocatalyst on the asymmetric membrane surface and pores insures simultaneous pollutant retention and photodegradation, permitting continuous long-term device operation without fouling, practical absence of concentrated retentate and cost effective production of clean water. Focusing on recent investigations of our group concerning the use of innovative titania nanostructured photocatalysts, the present work attempts to explore novel trends and present perspectives of TiO2 photocatalysis inside and outside the well-established frame of advanced oxidation processes (AOPs), expanding the field borders by including advanced reduction processes (ARPs) and relating technological applications (ARTs).